Strategi Pemberdayaan Komunitas Dalam Sistem Perlindungan Anak Dan Perempuan Yang Diprakarsai Oleh Dinas Pemberdayaan Perempuan Dan Anak - Zakaria, Zakaria (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2025)
This study aims to analyse community empowerment strategies in the child and women protection system initiated by the Women and Children Empowerment Agency (DPPA). The methods used are normative and empirical. The normative method examines the legal basis and policies related to the protection of women and children, while the empirical method explores field data through interviews, observations, and documentation of agency officials and community leaders. The results of the study show that community empowerment plays an important role in strengthening the social protection system for women and children. Through a participatory approach, the DPPA has succeeded in building synergy with the community in preventing violence and increasing legal awareness. However, there are still obstacles such as limited human resources, cross-sector coordination, and budget support. Overall, the community empowerment strategy by the DPPA is an effective and sustainable measure to create a safe, child-friendly, and gender-responsive environment.